Cucurbituril: A promising organic building block for the design of coordination compounds and beyond - Lü, Jian; Lin, Jing-Xiang; Cao, Min-Na; Cao, Rong (Coordination chemistry reviews, 2013)
This review article summarizes the recent development in the coordination chemistry of cucurbituril. Coordination compounds of cucurbituril with metal cations, including alkali/alkaline-earth metals, transition metals, and lanthanides, as well as polyoxometalates/metal-oxide anions/oxidechalcogenide clusters, have been extensively interpreted. [Display omitted] ► We introduce the recent development in the coordination chemistry of cucurbiturils. ► Various coordination compounds of cucurbiturils and metal cations are presented. ► Hybrid solids of cucurbiturils and cluster anions have been extensively interpreted. ► Applications of cucurbit[n]urils complexes are briefly highlighted. The structural determination and functional properties exploration of new coordination compounds is a contemporary theme of research topics in multi-discipline realms that attract interest from chemists and materials scientists. The trick of creating new coordination compounds relies on finding an extraordinary organic entity which has the ability to coordinate with metal ions, and, at the same time, bears functional properties. In this review article, the main types of coordination compounds in which cucurbiturils act as functional organic building blocks and interact with a wide range of metal ions through the portal carbonyl oxygen atoms have been summarized. Moreover, structural features of cucurbituril coordination compounds with different metal cations, including alkali/alkaline-earth metals, transition metals, and lanthanides, as well as metal containing clusters (polyoxometalates/metal-oxide/chalcogenide clusters), have been identified. The roles of cucurbiturils in the self-assembly of coordination compounds and other factors such as electron configurations of cations and anion species have been interpreted. The on-going applications based on the concept of coordination chemistry in catalysis and materials science have also been highlighted.